The relationship of some kinematic variables of the fixed foot and body and the accuracy of scoring while performing penalty by futsal players - Qadr, N. A. (Sports Science and Health, 2018)
There is a difference in terms of the views of coaches and specialists regarding the fixed foot and position of the body. No study has been noted on futsal in which the variables of the kinematics of the fixed foot and body were analyzed. These variables have a significant importance in terms of the angle of fixed foot and body and their direction and distance. They are important in order to be accurate in scoring and specifically in the fixed balls. The objective of the study was to identify the relationship of some kinematic variables of the fixed foot and body to the accuracy of scoring when performing penalty by futsal players. The research participants were the team of the University of Koya for the academic year 2016-2017. The researcher chose the sample by deliberate method and reached 13 players. Each player has played for at least four years, and all players use the right foot, while the the average age of sample is 23.4 years, body mass 67.37 kg, body height 171 cm, and leg length 93.76 cm. The conclusions of the researcher are that the fixed foot as other parts of the body have an effective role during the scoring of a fixed ball in the game of futsal. The direction angle of the fixed foot has an impact on the mechanical axis of the body and is reflected on the accuracy of the scoring in fixed balls in futsal.